Application of EOQ, Safety Stock and ROP methods in the Information System for Production of Raw Materials - Nugraha, Ucu; Lestari , Sri; Rijayana, Iwan; Rijayana, Murnawan; Mardiana, Siti; A.E. Virgana Targa Sapanji, R.; Samihardjo, Rosalin (International Journal of Psychosocial Rehabilitation, 2020)
The raw material inventory management process is very important because if raw materials that are not durable are stored for too long causing damage so this results in losses for the company. Inventories can be controlled using the Economic Order Quantity (EOQ) method. This method can produce calculations of economic order quantities with minimal costs. An information system with an EOQ calculation function to control the amount of raw materials from the inventory process using the EOQ method by considering Safety Stock and Reorder Points (ROP), and presenting accounting reports in the form of journals, ledgers, purchasing reports and production data reports. The implementation of EOQ by considering Safety Stock and RO in the information system will make it easier for companies to control the available raw materials.